The Influence of Women’s Economic Decision-making Power on Achievements in the Millennial Group: A Case Study of Chang Noi Sub-district, Bang Sai District, Phra Nakhon Si Ayutthaya Province - Kaithong, Benjapa (Journal of Community Development Research (Humanities and Social Sciences); Vol 17 No 3 (2024): July - September 2024DO - 10.14456/jcdr-hs.2024.21, 2024)
The objectives of this research are 1) To study the levels of economic decision-making power and the levels of achievement of millennial women in Chang Noi sub-district, Bang Sai district, Phra Nakhon Si Ayutthaya province, and 2) To examine the influence of the levels of economic decision-making power on the levels of achievement among millennial women. The researcher used quantitative research, collected data through questionnaires verified by qualified experts, and tested reliability using the Cronbach’s alpha coefficient with a threshold of 0.6 and above. Millennial women, aged between 22-40 years, were the sample group, with a total of 150 questionnaires distributed and collected. Data analysis was performed using mean, standard deviation, and multiple regression to answer the research objectives.           The research findings indicate that the variables–such as economic decision-making power (IV) and achievement (DV)– overall fall within the moderate level and high level respectively. Furthermore, the overall analysis results suggest that the levels of decision-making power have a positive influence on the levels of achievement (such as self-esteem, income and asset growth, and fair job access) among millennial women. When considering each factor (IV), it was found that the levels of labor market entry have a positive influence on women’ achievements. On the other hand, levels of household economy and levels of access to financial resource do not have any positive influence on women’ achievement. Keywords: Economic Decision-making Power, Achievements, Millennial Women, Labor Market Entry, Income and Asset Growth